Análisis de la accesibilidad turística en huéspedes con movilidad reducida del Hotel Camino Real del cantón Montalvo - Varela Gaibor, Victor Hugo (2021)
People with reduced mobility have the right to stay in establishments that provide them with inclusion, accessibility must be incorporated by all tourism service providers, contributing to the development of tourism and generating greater demand in cities. Allowing inclusion in accommodation establishments will guarantee a difference from the competition and preference for guests with reduced mobility. The current case analysis seeks to analyze the accessibility of guests with reduced mobility of the Camino Real hotel in the Montalvo canton, for which an observation sheet was made, considering the Guide for Lifting the Accessibility File belonging to Ecuador and the manual of Accessibility Guidelines in Tourist Accommodation. Through the observation file, surveys and interviews, an analysis was carried out that determines that the Camino Real hotel lacks infrastructure, equipment, accessories and people trained to host tourists with reduced mobility.